Synthesis and characterization of 1,3,4-oxadiazoles bearing an indole ring - Ng, Yu Xuan (2020)
1,3,4-oxadiazoles are important in various fields and have been involved in many studies by researchers. 1,3,4-oxadiazoles have many biological activities, for example, antifungal, antibacterial and anti-oxidant activities. A carboxylic acid hydrazide was synthesized from the reaction between an indole ester and a hydrazine hydrate and used as a starting material of 1,3,4-oxadiazole derivatives. There were four 1,3,4-oxadiazoles being synthesized in this project. The 1,3,4-oxadiazole derivatives were synthesized from carboxylic acid hydrazide reacted with different benzoic acid derivatives with the presence of POCl3. The percentage yields for the synthesized 1,3,4-oxadizoles were between 8% to 70%. For the characterization of the carboxylic acid hydrazide and the 1,3,4-oxadiazoles were using various instruments such as melting point apparatus, FT-IR, 1H NMR,13C NMR , DEPT, HMQC, and HMBC.